Physicochemical properties, preliminary characterization, and assessment of potential bioactivities of polysaccharide purified from the leaves of Avicennia marina. (August 2021) - Jha, Natwar; Sivagnanavelmurugan, Madasamy; Prasad, Prema; Lakra, Avinash Kant; Ayyanna, Repally; Domdi, Latha; Arul, Venkatesan
Abstract: A low molecular weight polysaccharide, the AMLP was isolated from the leaves of Avicennia marina and sequentially purified using DEAE-Sepharose fast flow and size exclusion chromatography. Monosaccharide analysis suggested that AMLP is mainly composed of fucose (38.34 %), galactose (30.16 %), mannose (13.32 %), and rhamnose (18.18 %). IR spectroscopy and High-performance size-exclusion chromatography (HPSEC) analysis revealed that AMLP was a sulfated homogenous heteropolysaccharide, and their molecular weight observed was 1.31 kDa. The Spectroscopic analysis of AMLP comprised of (1, 2)- α-L-Fuc p, (1, 6)-β-D-linked galactan, α-rhamnose, and (1, 4)-β-D mannose residues. AMLP has a loosely arranged granular bead-like appearance present on the surface and also with the presence of some porous structures. The rheological properties of AMLP exhibited pseudoplastic properties with shear-thinning flow behavior. Congo red test and X-ray diffraction (XRD) results indicated the semi-crystalline nature of AMLP with a triple-helical structure. Thermogravimetric and Differential scanning calorimetry (TGA-DSC) analysis of AMLP found was thermally stable and its degradation temperature observed was 280 °C. Furthermore, AMLP exhibited potential antibacterial and antibiofilm properties against bacterial pathogens such as Listeria monocytogenes, Escherichia coli, Klebsiella pneumonia, Salmonella typhimurium, and Staphylococcus aureus . The In vitro antioxidant activities such as DPPH scavenging, Superoxide radical scavenging, OH radical scavenging, and reducing power activities of AMLP were evaluated and the results revealed that the tested antioxidant activities of AMLP were significantly (P < 0.05) increased with increasing the concentrations. Overall, these findings suggested that AMLP could be used as a potential candidate in pharmaceutical, cosmetics, and food industry applications. Graphical abstract: Image 1 Highlights: AMLP (polysaccharide) from the leaves of Avicennia marina mangrove plant was characterized. The backbone of AMLP contains (1, 2)-α-L-Fuc p, (1, 6)-β-D-linked galactan, α-rhamnose and (1, 4)-β-D mannose residues. It shows pseudoplastic flow properties with shear thinning behavior in solution. AMLP showed triple-helix conformation and high thermal stability with degradation temperature of 280 °C. It showed promising antioxidant activity and antibiofilm activity against several pathogens.